Synthesis, NMR spectroscopy and crystal structures studies of novel 2-amino-N-(2-benzyloxy-3-methoxybenzylidene) aniline - Al-Douh, Mohammed Hadi; Osman, Hasnah; Abd Hamid, Shafida (icic-bme, 2009)
The reaction of benzyl o-vanillin 1 with ophenylenediamine 2PD, in dichloromethane at low conditions produced novel amino benzeneamine: 2-amino-N-(2-benzyloxy-3- methoxybenzylidene) benzeneamine 2. The intermediate 2 is isolated and obtained as single crystals and their structures were determined and studied by x-ray crystallography. The complete assignments of 2 were made using FTIR, HRMS, 1D and 2D NMR including 13C, COSY, HMQC and HMBC in CDCl3 and will be discussed.